Selective nourishing of gut microbiota with amino acids: A novel prebiotic approach? - Beaumont, Martin; Roura, Eugeni; Lambert, William; Turni, Conny; Michiels, Joris; Chalvon-Demersay, Tristan (Frontiers in Nutrition, 2022)
Prebiotics are dietary substrates which promote host health when utilized by desirable intestinal bacteria. The most commonly used prebiotics are nondigestible oligosaccharides but the prebiotic properties of other types of nutrients such as polyphenols are emerging. Here, we review recent evidence showing that amino acids could function as a novel class of prebiotics based on: i) the modulation of gut microbiota composition, ii) the use by selective intestinal bacteria and the transformation into bioactive metabolites and iii) the positive impact on host health. The capacity of intestinal bacteria to metabolize individual amino acids is species or strain specific and this property is an opportunity to favor the growth of beneficial bacteria while constraining the development of pathogens. In addition, the chemical diversity of amino acids leads to the production of multiple bacterial metabolites with broad biological activities that could mediate their prebiotic properties. In this context, we introduce the concept of “Aminobiotics”, which refers to the functional role of some amino acids as prebiotics. We also present studies that revealed synergistic effects of the co-administration of amino acids with probiotic bacteria, indicating that amino acids can be used to design novel symbiotics. Finally, we discuss the difficulty to bring free amino acids to the distal gut microbiota and we propose potential solutions such as the use of delivery systems including encapsulation to bypass absorption in the small intestine. Future studies will need to further identify individual amino acids, dose and mode of administration to optimize prebiotic effects for the benefit of human and animal health.